Role of Digitalization in Documentation and Preservation: An Application of Industry 4.0 - Sumit Rastogi, Rachita Kapoor Bhasin, Priyanshi Sharma (Journal of Informatics Education and Research, 2024)
In a time characterized by the swift progression of technology, the role of digital documentation has grown to be essential within contemporary society. This section delves into the importance of digital documentation and the hurdles linked with its conservation, examining the strategies, optimal approaches, and up-and-coming innovations that enable the enduring protection of digital resources. The procedures used to make sure that digital materials remain accessible are referred to as "digital preservation." Finding means to re-present what was initially displayed to consumers using a combination of hardware and software technologies operating on data is necessary to do this. To achieve this, it is necessary to comprehend and manage digital objects on four different levels: as physical occurrences, as logical encodings, as conceptual objects with meaning for humans, and as collections of fundamental components that must be preserved in order to provide future users with the object's core. All the procedures designed to maintain the availability of digital historic resources for as long as they are required can be grouped under the umbrella term of digital preservation. The loss of access is one of the biggest challenges to digital continuity. If the means of access have been lost and access is no longer feasible, then it is difficult to say that digital materials have been saved. To sustain accessibility—the capacity to reach their core, genuine message or purpose—digital resources must be preserved.